Analisis Pengaruh Informasi Laporan Keuangan terhadap Keberlanjutan Laba (Earnings Sustainability) pada Lembaga Keuangan Syariah - Dayun Mahesa Dewi Adam; Prayogo P. Harto (Jurnal Akuntansi dan Keuangan Islam, 2015)
The issue will be discussed is the effect of financial information to earningssustainability that focuses on case studies of BSM. Operating profitof BSM wasfluctuated from year to year, so it is necessary to know the extent of effect fromfinancial information to reflects the rate of profit. Financial information that is usedare the components of financial statements, that: Operating Cash Flow (AKO),Temporary Syirkah Funds (DST), and Zakat of BSM (ZAKAT) as the independentvariable and Operating Income (LO) as the dependent variable. The method ofanalysis used in this research is the multiple linear regression analysis and through thetesting phase of classical assumption that the testing conducted on the annual financialstatements of BSM that the years start from 1999 to 2013. Multiple regression resultsshow that all the independent variables as the information of financial statement inthis study had a positive and significant influence to the dependent variable,sustainability earnings. So it can be concluded that information of financial statementshave an important role in assessing the sustainability earnings of BSM.